2017
DOI: 10.1590/1806-9061-2016-0245
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Genotypes and Heat Tolerance of Commercial and Native Chickens Reared in Hot and Humid Conditions

Abstract: Heat tolerance in poultry production was obtained attention due to the need for genetic lines that can withstand climate changes. This study aimed at investigating heat tolerance in commercial and native broiler genetics, as well as the physiological and growth performance responses of HSP70 genotypes submitted to heat stress. In Experiment I, heterophil:lymphocyte (H:L) ratio, as an indicator of heat tolerance, was compared between commercial broilers (n = 100) and Thai native chickens (n = 100). Growing chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
7
28
0
1
Order By: Relevance
“…However, there was not such an action on H:L ratio of NO 500 group. Duangjinda, Tunim, Duangdaen, and Boonkum () reported that the H:L ratio was increased after week 1 of heat exposure in chickens but tended to recover to normal levels after 3 weeks of heat exposure because of homoeostasis. Although we only have data up to the end of week 6 of the feeding trial, the H:L ratio might also have been recovered in our chicks by homoeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was not such an action on H:L ratio of NO 500 group. Duangjinda, Tunim, Duangdaen, and Boonkum () reported that the H:L ratio was increased after week 1 of heat exposure in chickens but tended to recover to normal levels after 3 weeks of heat exposure because of homoeostasis. Although we only have data up to the end of week 6 of the feeding trial, the H:L ratio might also have been recovered in our chicks by homoeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was not such an action on H:L ratio of NO 500 group. Duangjinda, Tunim, Duangdaen, and Boonkum (2017) reported that the H:L ratio was increased after week 1 of heat exposure in chickens but tended to recover to normal levels after 3 weeks of heat exposure because of homoeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the detected alleles (hsp70-1, hsp70-2, and hsp70-3) were associated with the nature of resistance to heat stress, and therefore, it's potential to be used as a candidate gene for heat stress (Mazzi et al, 2003). The results of this study have encouraged additional research in the other chickens: Indonesian local chicken (Tamzil et al, 2013a), Taiwanese local chicken (Liang et al, 2016), and Thailand local chicken (Duangjinda et al, 2017).…”
Section: Introductionmentioning
confidence: 74%
“…Genotyping and allelic frequency variation of HSP70 gene by Liang et al, (2016) indicated that AA genotype has greater heat tolerance after acute heat stress in the indigenous Taiwanese chickens. Results of HSP70 gene genotyping by Duangjinda et al, (2017) using CfrI restriction enzyme also are indicated that C2C2 chickens were less tolerant to heat stress compared to other genotypes.…”
Section: Discussionmentioning
confidence: 97%
“…PCR primers of chickens HSP70 gene and HSP90β gene is described in table (1). Forward and reverse primers of HSP70 gene were used to amplify 360 bp from the beginning of the coding region and EaeI restriction enzyme was used for genotyping polymorphisms in this region as described by (Duangjinda et al, 2017). On the other hand, HSP90β gene Primers were used to amplify 498 bp from the 5' flanking region and exon 2 of this gene, and polymorphisms in this region was genotyped by using MspI restriction enzyme according to (Chen et al, 2013).…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymomentioning
confidence: 99%